Lack of insurance coverage and urgent care use for asthma: A retrospective cohort study - Andresen Elena M; Markovitz Barry P (BMC, 2006)
Abstract Background Asthma is a common chronic disease with profound impacts upon individuals and the US health care system. Inadequate health care coverage has been associated with more frequent and severe exacerbations of the disease. We examined the relationship between adequacy of health care coverage and use of emergent care of adults with asthma. Methods The 2001 Behavioral Risk Factor Surveillance System was the source of data on adults with current asthma. Bivariate and multiple logistic regression analysis modeled identifiable factors in predicting urgent or emergent care. Results Key variables included demographics and information on self-reported gaps in health care coverage. The primary outcome was emergency room or urgent care visits for worsening of asthma symptoms. Of 16,234 subjects nationally with current asthma, 2,195 from eight states had valid responses to a supplemental module asking about emergency room use or urgent care visits because of asthma. Thirty four percent of these individuals required such care in the previous year. Having an interruption in health care coverage in the past year was associated with an increased risk of needed urgent or emergent care (crude Odds Ratio [OR] 1.48, 95% confidence intervals [CI]1.03, 2.1). The association was not statistically significant in the adjusted multivariate model including race/ethnicity, employment status, gender, age, education and the ability to identify a primary physician (adjusted OR 1.2, 95% CI 0.8, 1.8). Conclusion This study provides population-level, generalizable evidence of increased risk of exacerbations of asthma in adults and (1) their demographic characteristics, and (2) continuous adequate health care coverage.